Ensino médio integrado no ceará: construção da escola em tempo integral - Maia, José Eduardo Nobre (Universidade Federal Rural do Semi-Árido, 2020)
The present dissertation was intended to analyze the curricular and political reconstruction of the school proposal in full time, in the comprehension of the school context itself. The general objective of the study was: to analyze the challenges and possibilities for the construction of a full time school through the construction of high school integrated in the public school of Ceará. This objective was supported by the following specific objectives: a) Discuss the specificities of the teaching proposal based on the Full-time High Schools (EEMTI); b) Discuss the process of curriculum structuring of EEMTI; c) Evaluate the contributions and results of the process of building the EEMTI in a state school already established by the program; and d) To analyze the repercussions of the construction of the EEMTI from the perspective of managers and teachers, for the understanding of the unfolding in the teaching process and the processes of resignification. The theoretical-methodological scope of the study was the basis proposed by the Ball Policy Cycle approach. In this case study, we used a qualitative perspective with three approaches to data construction: document analysis, on-site observations and semi-structured interviews; and a quantitative approach, based on an analysis of the numerical results of the proposal. In this endeavor, contributions were produced from a poststructuralist theoretical view, seeking to understand the field of teaching resignifications, which express themselves as practices linked to policy cycles that intercommunicate and dispute between themselves formations of meanings. The information provided provided relevant data for the construction of important reflections, especially regarding the demands to face the challenges of the fulltime public school, as well as the strategies of policy reconstruction in each distinct school territory. Therefore, it is necessary to consider the experiences, opinions and different perspectives of all actors involved in politics, understood as active participants in the process of its construction, and it is necessary to understand and analyze politics as a practice. It seems feasible, therefore, to assert that full-time success comes not from the policy text, with its perfect goals and objectives, but from the action of managers, coordinators, teachers, students, and other community participants in carrying out creative and improvised actions and reconstructions. with the resource assigned to them.
Keywords: Educação integral; Tempo integral; Ensino Médio; Ceará; Integral education; Full-time; High school; Ceará; MULTIDISCIPLINAR::ENSINO